Optimal Acceptance Sampling Plans for Auditing "Batched" Stop and Go vs. Conventional Single-Stage Attributes Plans. - Maxim, L. D.; Cullen, D. E.; Cook, F. X. (The Accounting Review, 1976)
Abstract The article focuses on acceptance sampling plans for auditing. The interest in statistical sampling among accountants has become more pronounced and has broadened from problems of acceptance sampling to include techniques of statistical estimation. The paper contains a brief review of concepts, design and construction of both single sampling plans (SSP) and sequential sampling plans and presents a new cost optimization model with illustrative results for selection of the least-cost sampling plan. Throughout the paper, authors assume that the population is large relative to the sample size. Acceptance sampling consists of drawing samples or groups of samples from a population, examining these for properties of interest and finally, reaching some decision based upon the sample results. Elements of an acceptance-sampling plan are the method of sampling, the sample sizes and the appropriate decision rules for reaching some decision. The simplest acceptance sampling plan, an SSP, consists of the selection of a random sample of N items; the determination of the number of errors or defectives; and comparison of this quantity, with a previously determined acceptance number, or rejection number.